2020
DOI: 10.1590/s0004-2803.202000000-18
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Aspects in Brazilian Celiac Women

Abstract: BACKGROUND: Celiac disease (CD) is a chronic enteropathy in response to ingestion of gluten. CD was associated with gynecological disorders. OBJECTIVE: In this retrospective study, we aimed to investigate the age of menarche, age of menopause, number of pregnancies and abortions in Brazilian celiac patients. METHODS: We studied 214 women diagnosed with CD and as control group 286 women were investigated. RESULTS: Regarding the mean age of menarche, a significant difference was found (12.6±1.40 in CD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In our study, psychiatric and neurological symptoms, which are common in this age group, could be part of the CD spectrum of manifestations, similar to those described by other authors 16,17 The risk of complications is higher in patients with late recognition of CD because gluten testing is more time-consuming 2 . We observed that anemia and bone disorders were more frequent.…”
Section: Gastrointestinal Segment N (%)supporting
confidence: 89%
“…In our study, psychiatric and neurological symptoms, which are common in this age group, could be part of the CD spectrum of manifestations, similar to those described by other authors 16,17 The risk of complications is higher in patients with late recognition of CD because gluten testing is more time-consuming 2 . We observed that anemia and bone disorders were more frequent.…”
Section: Gastrointestinal Segment N (%)supporting
confidence: 89%
“…Seven studies (5 cohorts) [ 34 , 35 , 37 , 40 - 42 , 44 ] were analyzed, including 7978 pregnant women with CD and 78,241 non-CD pregnant women; SA was detected in 11.5% (n=920) vs. 9.2% (n=7202), respectively. A statistically significant positive correlation was found between the risk for SA and CD (RR 1.35, 95%CI 1.10-1.65).…”
Section: Resultsmentioning
confidence: 99%
“…These include the aforementioned iron deficiency anemia, delayed menarche, decreased AMH levels or a family history of CD [1,12,20,21]. At the moment it seems unreasonable to perform screening tests in all patients diagnosed with infertility, but for patients with one of the above-mentioned ones, it is worth considering.…”
Section: Discussionmentioning
confidence: 99%
“…In literature some authors point out a link between untreated CD and delayed menarche [20] and early menopause [7]. A shorter reproductive period is a consequence.…”
Section: Celiac Disease and Fertilitymentioning
confidence: 99%
See 1 more Smart Citation